Knowing in all: or is it? some reflections on why the acquisition of knowledge, focussing particularly on evaluation activities, does not always lead to action - Cracknele, Basil E. (2001)
This article examines the factors that influence whether the acquisition of knowledge leads on to action. It looks first at the `supply' side, i.e. the kind of knowledge that is being acquired and whether it meets the needs of the intended users and is conducive to action; whether knowledge is a product or a process; the relevance of the positivist and constructivist approaches in this context; and whether participatory methods are required. The article then turns to the `demand' side, and looks at possible reasons why decision-takers may often seem to ignore new knowledge and evaluation findings. It suggests that evaluation may sometimes have unrealistic expectations of the kind of impact their reports should have. On the other hand there are factors leading to inertia and risk averseness that may stymie action. The importance of a `knowledge culture' is emphasized if knowledge is to be turned into action. - Reproduced.
Keywords: Knowledge; Sociology of knowledge